The Traditions of Sasak Tribe in Sade Village, Central Lombok, Indonesia - Alam Mahadika; Viqri Rahmad Satria (Indonesian Academy of Social and Religious Research (IASRR), 2021)
This study explains the local traditions of Sasak People in Sade Rembitan Village, Central Lombok, Indonesia. By using research methods in the form of qualitative descriptive analysis, the researchers collected the data through literature study from previous researches about Sasak traditions located in the Lombok Islands. The results of the research describe the sasak tradition, namely Ngayu Ayu Ritual. Ngayu Ayu ritual as a ritual to fight the devil that threat the harvest of Sasak people. Rituals of traditional birth ceremonies as a medium to ask for safety and gratitude for all the conveniences given by God. The implementation of this traditional birth ceremony as a religious ceremony symbolizes that every ritual performed with prayers. Furthermore, the tradition of eloping by the Sasak tribe known as Merariq, the tradition of abducting the Sasak people is a form of action that belongs to social action. It can be said to be a social action if it can affect or be influenced by others. Sorong Serah tradition is commonly found after the occurrence of Merariq (Eloping), Sorong Serah tradition is used to hand over krama aji which is a payment that has been agreed before the implementation of marriage and customary fines.